Inobservancia del debido proceso y seguridad jurídica en las sanciones impuestas a los socios por infracciones cometidas al estatuto social de la organización - GAONA VALDIVIESO, MERY ELIZABETH (2015)
This research work entitled "Failure to comply with due process and legal certainty in the sanctions imposed on members for offenses committed to the bylaws of the organization", its development is justified because there is violation of rights of the partners in the voluntary sector that is the whole constituted by natural person with similar or complementary productive in order to produce, market and consume goods and services lawful and socially necessary, auto supplies of raw materials, supplies, tools, technology, equipment and other goods economic activities associations, or market their produce in supportive way and self managed by the social organization that can be an association of manufacturers of bricks and tiles craftsmen, artisans association, etc. As the cooperative sector consists of the set of cooperative societies understood as people who have united voluntarily to meet their economic, social and cultural needs in common, through a jointly owned and democratically controlled, with personality concerns private law legal and social interest. These social organizations are regulated by the Superintendency of Popular Economy and Solidarity who know the cases of rights violations when in any social organization inobservan fundamental rights. There is now a serious problem with sanctioning regime of social organizations towards the partners that will enable the right of defense come to impose fines, suspend them from their activity, or in some extreme to exclude them from social organization cases without having given the opportunity to defend itself as required by the Constitution of the Republic, this creates legal uncertainty and violates due process. Therefore, you must force the authorities of the social organizations that comply with the law, otherwise should receive severe sanctions in order to follow a due process applying the law and without violating the rights of members. The development of literature and the results of the survey and interviews allowed me to get criteria, with clear and precise grounds of well known literature, which contributed to the verification of objectives, and the testing of the hypothesis, allowing support changes proposed to the Organic Law of the People and Solidarity Economy and Financial Sector Popular and Solidarity